A proposed student handbook for Atma Jaya Catholic University of Indonesia - Thio, Bernadette Sian Lie (Animo Repository, 1979)
This project paper comes up with a written Student Handbook for Atma Jaya University. Sources of data for this research were the written policies and regulations which were then in operation, Atma Jaya brochures, faculty and departmental circulars, the Rector's annual reports, Atma Jaya student profiles, and development policies of Atma Jaya University. Data were gathered and arranged systematically according to the topics which composed the content of the proposed Student Handbook: 1. History and Mission Statement of the University 2. Organizations of the Institute's administration 3. Policies and regulations on admission, general matters, financial matter, academic matters 4. Services: student personnel services and auxiliary services. Procedures intended to solve conflicting matters were also included in the proposal. The proposed Student Handbook further provided for follow-up steps for consultation and implementation.